2006
DOI: 10.1007/s10725-006-9130-6
|View full text |Cite
|
Sign up to set email alerts
|

Indole acetic acid (IAA) induced changes in growth, relative water contents and gas exchange attributes of barley (Hordeum vulgare L.) grown under water stress conditions

Abstract: Effect of different concentrations of indole acetic acid (IAA) under varying soil water deficit conditions on two barley cultivars viz. B-99094 and Jau-87 was investigated in soil filled earthen pots. There were six treatments including control each with four replicates. Three concentrations of IAA (0, 15 and 30 mg l -1 ) were applied as foliar spray 30 days after germination. After hormone application, half of the pots were subjected to one cycle of water stress (withholding of water till incipient wilting), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 7 publications
5
15
0
Order By: Relevance
“…The result of this study was in agreement with the findings of Awan and Alizat (1989), Sontakey et al (1991) and Reena et al (1999) who reported that IAA increased the seed yield of rice, sesame and soybeans respectively and Ashraf et al (2006) who reported that IAA was successfully used to enhance the growth and yield of barley cultivars. …”
Section: The Yield and Yield Componentssupporting
confidence: 92%
“…The result of this study was in agreement with the findings of Awan and Alizat (1989), Sontakey et al (1991) and Reena et al (1999) who reported that IAA increased the seed yield of rice, sesame and soybeans respectively and Ashraf et al (2006) who reported that IAA was successfully used to enhance the growth and yield of barley cultivars. …”
Section: The Yield and Yield Componentssupporting
confidence: 92%
“…Nitric oxide has been recognised as a new plant hormone because of its signalling functions involved in plant growth and development (Shapiro, 2005). So far, several plant hormones and their synthesised analogues including IAA, NAA, GA and ethephon have been successfully used to improve crop yields (Eriksson et al , 2000; Khan et al , 2002; Ashraf et al , 2006). In the present research, we demonstrated that application of low concentration of NO gas significantly improved the growth of spinach (Figs 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…Increases in the IAA concentration with decreasing water potentials were also reported by Darbyshire (1971) in tomato plants. It has been shown that exogenous applications of IAA alleviate the adverse effects of water stress and help stressed plants grow under unfavourable conditions (Gadallah 2000) by enhancing growth and photosynthetic efficiency (Ashraf et al 2006). However, Mahouachi et al (2007) observed that water stress did not significantly alter endogenous IAA levels in papaya seedlings.…”
Section: Environmental Effect On Proline and Phytohormonesmentioning
confidence: 99%